Waterborne Isolates of Campylobacter jejuni Are Able to Develop Aerotolerance, Survive Exposure to Low Temperature, and Interact With Acanthamoeba polyphaga - Shagieva, Ekaterina; Demnerova, Katerina; Michova, Hana (Frontiers in Microbiology, 2021)
Campylobacter jejuni is regarded the leading cause of bacterial gastroenteritis all around the world. Even though it is generally considered to be a sensitive microaerobic pathogen, it is able to survive in the environment outside of the intestinal tract of the host. This study aimed to assess the impact of selected environmental parameters on the survival of 14 C. jejuni isolates of different origins, including 12 water isolates. The strains were tested for their antibiotic resistance, their ability to survive at low temperature (7 °C), develop aerotolerance, and to interact with a potential protozoan host Acanthamoeba polyphaga. The antibiotic susceptibility was determined by the standard disk diffusion according to EUCAST. Out of the 14 isolates, 8 were resistant to ciprofloxacin and 5 to tetracycline, while only one strain was resistant to erythromycin. Five isolates were resistant to two different antibiotic classes. Tetracycline resistance was only observed in strains isolated from wastewater and clinical sample. Further, the isolates were tested for their survival at 7 °C under both aerobic and microaerobic conditions using standard culture methods. The results showed that under microaerobic conditions, all isolates maintained their cultivability for 4 weeks without a significant decrease in the numbers of bacteria and variation between the isolates. However, significant differences were observed under aerobic conditions. The incubation led to a decrease in the number of cultivable cells with complete loss of cultivability after 2 weeks (one water isolate), 3 weeks (7 isolates), or 4 weeks of incubation (6 isolates). Further, all isolates were studied for their ability to develop aerotolerance by repetitive subcultivation in microaerobic and subsequently aerobic conditions. Surprisingly, all isolates were able to adapt and grow under aerobic conditions. As the last step, 5 isolates were selected to evaluate a potential protective effect provided by A. polyphaga. Cocultivation of isolates with the amoeba resulted in survival of about 40 % of cells treated with otherwise lethal dose of gentamicin. Taken together, C. jejuni is able to adapt and survive in potentially detrimental environment for a prolonged time, which is emphasising the role of environmental transmission route in the spread of campylobacteriosis.